Anemia and iron deficiency in indigenous women from the Department of Presidente Hayes, Paraguay, 2010-2011 - Díaz, Valentina; Echagüe, Gloria; Páez, Malvina; Mendoza, Laura; Bongelós, Pamela; Castro, Amalia; Rodríguez, María Isabel; Jiménez, Graciela; Araujo, Patricia; Laspina, Florentina; Castro, Wilberto; Marecos, Ramón; et al. (Revista Chilena de Salud Pública, 2015)
According to UNICEF, between 4 thousand and 5 thousand million people in the world have ferropenia and it is calculated that 2 thousand million suffer from anemia. Women may present different types of anemia, due either to abundant menstruation or deficient iron intake. The objective of this work was to evaluate hematological and chemical parameters of anemia in indigenous women from the Department of Presidente Hayes, Paraguay, from October 2010 to October 2011. This was a cross-sectional, observational and descriptive study that included 222 women aged 12 to 60. years, belonging to the ethnic groups maká, nivaclé, sanapaná, enxet and tobaqom. Hemoglobin concentration and hematological parameters were determined using a hematological counter. Serum iron and transferrin were determined by a colorimetric enzymatic method, and transferrin saturation by manual calculation. In 40% (88/222) of the women, hemoglobin values under 12 g/dL were found. Hematological parameters were below established cut-off points in 33% of women for MCV, 22% for MCH and 16% for MCHC. These results indicate iron deficiency in different stages, which could have neg psychomotor development and cognitive function in children, as well as low academic performance and other pathologies, affecting a vulnerable population where most studied women were of a reproductive age